The Use of Semantic Distance Metrics to Support Ontology Audit - Wang, Jian (American Medical Informatics Association, 2010)
This study explored the possibility that semantic distance metrics can be used to develop methods for auditing biomedical ontologies. We developed and tested an approach using the Foundational Model of Anatomy (FMA) and the body-structure taxonomy of SNOMED CT. We evaluated 190 class pairs in human anatomical structures using three semantic distance metrics: simple edge count, normalized path length, and information content. We applied principal component analysis (PCA) to study relationships between the semantic distance measurements so produced in FMA and SNOMED CT. We found that our application of PCA could detect significant discrepancies, but not necessarily outright mistakes, in the two ontologies. A review of discrepancies revealed that they often relate to multiple design perspectives employed in ontological definitions.